2020
DOI: 10.1094/pdis-02-20-0391-re
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Oxathiapiprolin and Mefenoxam in Citrus Seedlings After Root Application and Implications for Managing Phytophthora Root Rot

Abstract: Oxathiapiprolin is highly effective in the management of Phytophthora root rot of citrus, however, its uptake into plants after soil application is not known. This was investigated and compared with mefenoxam using potted citrus seedlings sampled 7, 10, 13, and 16 days after soil treatments. Bioassays and liquid chromatography-tandem mass spectroscopy (HPLC-MS/MS) were used to quantify fungicide amounts in plant extracts. Distinct inhibition zones of mycelial growth of Phytophthora citrophthora were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Thereby, there would be a high risk of development of metalaxyl resistance in populations of P. boehmeriae in the field, when metalaxyl was long and continuously applied for the control of the diseases caused by P. boehmeriae, which could lead to the defeat in controlling plant blight with metalaxyl. In addition, it must be noted that mefenoxam, metalaxyl-M, is the more recent isomer of metalaxyl, contains a much higher concentration of the active enantiomer of the original metalaxyl, and is therefore effective in the field (Parra and Ristaino 2001;Rubin et al 2008;Hu and Li 2014;Lookabaugh et al 2018;Gray et al 2020;Gonzalez-Tobon et al 2020;Siegenthaler and Hansen 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, there would be a high risk of development of metalaxyl resistance in populations of P. boehmeriae in the field, when metalaxyl was long and continuously applied for the control of the diseases caused by P. boehmeriae, which could lead to the defeat in controlling plant blight with metalaxyl. In addition, it must be noted that mefenoxam, metalaxyl-M, is the more recent isomer of metalaxyl, contains a much higher concentration of the active enantiomer of the original metalaxyl, and is therefore effective in the field (Parra and Ristaino 2001;Rubin et al 2008;Hu and Li 2014;Lookabaugh et al 2018;Gray et al 2020;Gonzalez-Tobon et al 2020;Siegenthaler and Hansen 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, Fangxin Chen and Yongxia Qi contributed equally to this work. and due to selection pressure brought by a long use of the fungicide, developments of resistance to metalaxyl among members of the oomycetes, including the genus Phytophthora, have appeared in many countries (Café-Filho and Ristaino 2008;Gisi and Sierotzki 2008;Hu et al 2008;Pérez et al 2009;Lookabaugh et al 2018;Gray et al 2020;Gonzalez-Tobon et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…8 Gray et al investigated the comparative mobility and residues of oxathiapiprolin in citrus seedlings after soil applications according to the current standards accepted by the United States Environmental Protection Agency; the results indicated that oxathiapiprolin had potential to long residual activity and persistence in citrus crops. 9 Wang et al used QuEChERS combined HPLC−MS/MS to determine the residue of oxathiapiprolin in cucumber, and a dietary risk assessment was carried out to demonstrate a low health risk from oxathiapiprolin. 10 Although there were many reports and literature studies on the degradation of oxathiapiprolin in different environments and agro-products, most of them only focused on the residues of oxathiapiprolin racemate and ignored its enantioselectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Feng et al used the field data and dynamiCROP modeling to analyze the distribution, uptake, and translocation mechanisms of oxathiapiprolin in leafy vegetables (Chinese cabbage and lettuce) and herbaceous vegetables (cucumber and tomato) and evaluated the potential human exposure to its residues from consumption of these agro-products; the field trials indicated that the final human intake of oxathiapiprolin ranges between 10 –4 and 10 –3 kg intake /kg applied . Gray et al investigated the comparative mobility and residues of oxathiapiprolin in citrus seedlings after soil applications according to the current standards accepted by the United States Environmental Protection Agency; the results indicated that oxathiapiprolin had potential to long residual activity and persistence in citrus crops . Wang et al used QuEChERS combined HPLC–MS/MS to determine the residue of oxathiapiprolin in cucumber, and a dietary risk assessment was carried out to demonstrate a low health risk from oxathiapiprolin …”
Section: Introductionmentioning
confidence: 99%
“…It can be applied via foliar sprays, soil applications (e.g. in-furrow) or soil drenches and it is efficiently translocated throughout plant tissues in a variety of horticultural species (Cohen 2015(Cohen , 2020Qu et al 2016b), including perennial tree crops (Gray et al 2020). In addition, oxathiapiprolin has low phytotoxic effects in host tissue.…”
Section: Introductionmentioning
confidence: 99%